The Commentators' Bible: Genesis : The Rubin JPS Miqra'ot Gedolot - Carasik, Michael; Carasik, Michael (Book collections on Project MUSE., 2018)
The biblical commentaries known as Miqra'ot Gedolot have inspired and educated generations of Hebrew readers. With the publication of this edition--the final volume of the acclaimed JPS English edition of Miqra'ot Gedolot--the voices of Rashi, Ibn Ezra, Nachmanides, Rashbam, Abarbanel, Kimhi, and other medieval Bible commentators come alive once more, speaking in a contemporary English translation annotated for lay readers. Each page in The Commentators' Bible: Genesis: The Rubin JPS Miqra'ot Gedolot contains several verses from the book of Genesis, surrounded by both the 1917 and the 1985 JPS translations and by new contemporary English translations of the major commentators. The book also includes a glossary of terms, a list of names used in the text, notes on source texts, a special topics list, and resources for further study. This large-format volume is beautifully designed for easy navigation among the many elements on each page, including explanatory notes and selected additional comments from the works of Bekhor Shor, Sforno, Gersonides, and Hizkuni, among others.